Modified Hemocorrection in the Complex Treatment of Patients with Pyoinflammatory Lung Diseases - V. V. Gavrikov; V. T. Dolgikh; K. K. Kozlov (Общая реаниматология)
Objective: To evaluate the efficiency of extracorporeal hemocorrection used in the complex therapy in patients with a pyoinflammatory process in the lung.Materials and methods: 62 patients, including 22 patients with lung abscess who underwent routine plasmapheresis and 40 patients with varying pyoinflammatory lung diseases who received modified hemocorrection — plasma exchange combined with laser extracorporeally washed-off cytomass irradiation, were examined and treated. The severity of their general condition was assessed by the SAPS scale and the severity of intoxication was evaluated by the content of low and medium-molecular weight substances (LMMWSs). The hemostatic system was studied by standardized studies.Results. Routine plasmapheresis was established to produce no impact on platelet functional activity within the first 24 hours and, three days later, promoted the progression of disseminated intravascular coagulation. A combination of plasma exchange and laser extracorporeally washed-off cytomass irradiation in patients with pyoinflam-matory lung diseases was attended by a lower blood coagulative activity and plasmin stabilization with attenuated throm-binemia. The plasma and erythrocytic levels of LMMWSs decreased and their urinary concentrations increased, which is indicative of the body’s detoxification block disorders irrespective of the severity of the disease.Conclusion. It is expedient to apply the plasma-exchanging technique in combination with laser extracorporeally washed-off cytomass irradiation to patients with the uncomplicated and complicated course of pulmonary pyoinflammatory processes without the signs of multiple organ dysfunction on admission to a specialized hospital.